Fight 'acceptable' with 'acceptable:' football, cultural battle in Turkey and the story of two 'doxas' over an old military song. Issue 1 (9th October 2020) - Irak, Dağhan
Abstract: Football, as other cultural products, has become a major part of the political field, since there has been an ongoing cultural battle between the President Recep Tayyip Erdoğan and his dissidents. The country is divided into two, not only between social and cultural capital owners; two sets of ideological elements, namely 'doxas' in reference to Bourdieusian sociology, also define the political faultlines in Turkey. Football, imported in the final years of the Ottoman Empire by the modern elite, has been intertwined with Turkish modernism and its core elements, such as nationalism. The Erdoğan regime, while dismantling the old rule, has also tried to create cultural hegemony, which has been met with dissidence. This paper analyses the role of an old military song called the 'Izmir March', sung in the football stands against the Erdoğan regime, discussing the elements of the two doxas in Turkey, old and new.